Measurement of Ce(IV) Concentration and Oxidation of Ce(III) in Foam Decontaminant - Jung, Chong-Hun; Choi, Wang-Kyu; Moon, Jei-Kwon (Asian Journal of Chemistry, 2017)
In order to regenerate Ce(III) to Ce(IV) in nanoparticle-based foam decontaminant containing tetrapropylenebenzene sulfonate (TBS) surfactant, it is necessary to determine the optimal conditions for ozonation treatment. The research was carried out to determine whether the potentiometric titration method can be used for an analysis of Ce(IV) concentration in nanoparticle-based foam decontaminant. Potentiometric titration with Fe(II) is able to effectively analyze the concentration of Ce(IV) in nanoparticle-based foam decontaminant containing a surfactant regenerated through ozonation treatment. The oxidation conversion rate of Ce(III) was increased with an increase in the flow rate of the gas mixture and ozone injection amount. The oxidation time for 100 % oxidation conversion of Ce(III) at an ozone injection amount of 9.0 and 7.5 g/h was 6.0 h and 7.0 h, respectively. The time required for 100 % oxidation conversion of Ce(III) to Ce(IV) at a specific ozone injection amount can be predicted from these experimental data.